The effects of ischemic preconditioning on aerobic and anaerobic variables associated with submaximal cycling performance - Clevidence, M. W.; Mowery, R. E.; Kushnik, M. R. (European Journal of Applied Physiology, 2012)
Acute limb ischemia induced by pressure cuffs before activity (ischemic preconditioning; IPC) has been reported to improve exercise performance at maximal efforts. The purpose of this investigation was to determine the effects of IPC during a submaximal performance test in competitive amateur level cyclists. Twelve healthy, male cyclists participated in two performance tests in which they cycled at successive relative intensities of 30, 50, and 70% of their maximal power output for 5 min each. The test culminated with an intensity of 90% of their maximal power output until exhaustion. Prior to each test, subjects randomly completed a control (CON) or IPC treatment. The IPC treatment consisted of alternating 220 mmHg of pressure applied by a cuff to the proximal portion of both thighs for 3, 5 min bouts separated by 5 min of rest. In addition to performance time to exhaustion, variables associated with aerobic performance (oxygen consumption, ventilation, respiratory exchange ratio, heart rate, and blood lactate) were measured continuously throughout the performance test. Statistical comparisons of data were made with repeated measures analyses of variance or paired T tests and significance was accepted as P < 0.05. Heart rate at the 30% relative intensity was significantly higher for the IPC treatment, but there were no other statistically significant differences between the control and IPC treatments across all variables and relative intensities. In this group of competitive amateur-level cyclists, an acute treatment of IPC did not improve performance at each submaximal intensity or increase time to exhaustion.